SIKAP GURU DAN TENAGA PENDIDIK TERHADAP ANAK USIA DINI YANG BERKEBUTUHAN KHUSUS - Mariyana Widiastuti; Yeny Duriana Wijaya; Sandfreni . (MOTORIC, 2021)
The aims of this study was to determine the attitudes of teachers and educators in dealing with early childhood who have special needs in the learning process in the classroom. This type of research is a quantitative descriptive study. The data in this study were obtained through observation, interviews, and surveys using an attitude scale that measures cognitive, affective, and behavior of teachers and educators towards early childhood with special needs. The results showed that 17 subjects had good knowledge about children with special needs, 17 subjects (100%) had bad emotions towards children with special needs, and 17 subjects (100%) had bad behavior towards children with special needs.